An Open-Label, Nonplacebo-Controlled Study on Cistanche tubulosa Glycoside Capsules (Memoregain®) for Treating Moderate Alzheimer's Disease. (June 2013) - Guo, Qihao; Zhou, Yan; Wang, Chao-Jih; Huang, Young-Ming; Lee, Yi-Ta; Su, Muh-Hwan; Lu, Jiahong
Aim: Efficacy and safety of Cistanche tubulosa glycoside capsules (CTG capsule, Memoregain ® ) for treating Alzheimer's disease (AD) were studied. Methods: A total of 18 patients with AD administered with Memoregain ® for 48 weeks were assessed for drug efficacy by Alzheimer's Disease Assessment Scale–cognitive subscale (ADAS-cog), Mini-Mental State Examination (MMSE), Activities of Daily Living (ADLs), Blessed Behavioral Scale, and Clinical Global Impression (CGI) scales. Results: The MMSE score was 14.78 ± 2.51 at baseline and 14.06 ± 4.26 at study completion. While changes in ADAS-cog score before and after 48 weeks of treatment were statistically insignificant, the score improved, deteriorated, and remained unchanged in 10, 7, and 1 patients, respectively. The ADL and CGI scores showed no significant difference from baseline. All adverse reactions were mild. Conclusion: After Memoregain ® treatment, patients with AD showed no obvious aggravation of cognitive function, independent living ability, and overall conditions but were stable throughout the study. Comparison with other long-term medications with acetylcholinesterase inhibitors suggests that Memoregain ® has a potential to be a possible treatment option for mild to moderate AD. Large trials with bigger population are required to confirm.